Genome‐wide association analysis of drought adaptive traits in common bean. Issue 5 (26th June 2021) - Dramadri, Isaac O.; Nkalubo, Stanley T.; Kramer, David M.; Kelly, James D.
Abstract: Genome‐wide association study (GWAS) was conducted to determine the genetic architecture of yield component and photosynthetic (PS) traits in 256 common bean ( Phaseolus vulgaris L.) genotypes from the Andean gene pool. The panel was evaluated under drought stress (DS) and non‐stress (NS) conditions at two locations for two seasons in Uganda and genotyped with 260K single nucleotide polymorphism (SNP) markers. Significant association signals were detected for yield component and PS traits on chromosomes Pv02, Pv03, Pv04, Pv06, Pv09, Pv10, and Pv11. Colocalized GWAS signals were detected for pod weight per plant (PW) and seed yield per plant (SY) on Pv06 with ten significant markers and for PhiNPQ, LEF, Phi2, and PhiNO on Pv11 under DS. Positional candidate genes were identified within the 1.76 Mb common region for PW and SY under DS on Pv06 including Phvul.006G117500, Phvul.006G119800, and Phvul.006G130500 annotated as plant invertase/pectin methylesterase inhibitor (INH/PMEI) superfamily protein, involved in sucrose metabolism and signaling. Phvul.006G121200, 14.9Kb upstream of marker S06_23021418 (23.02Mb) on Pv06, encodes Protein phosphatase 2C family protein involved in ABA signaling pathway. Positional candidate genes for PS traits PhiNPQ, LEF, Phi2, and PhiNO on Pv11 under DS were identified including Phvul.011G178200, Phvul.011G178250, Phvul.011G178300, and Phvul.011G178500 between 48.94–49.96 Mb annotated as "RING/U‐BOX SUPERFAMILY PROTEIN", ubiquitin ligase (E3) involved in ABA‐mediated responses. Significant markers associated with colocalized GWAS signal for SY and PW on Pv06 identified in this study can be validated for marker assisted breeding to improve drought tolerance in large‐seeded Andean beans. Core Ideas: Genomic regions important for drought tolerance in large‐seeded beans were identified Yield traits did not associate with photosynthetic traits Candidate genes associated with ABA signaling pathway appear important in drought tolerance